Towards full digital inclusion: the ENTELIS manifesto against the digital divide. Issue 3 (19th September 2016) - Mavrou, Katerina; Hoogerwerf, Evert-Jan
Abstract : Purpose: The purpose of this paper is to present the work of the European Network for Technology Enhanced Learning in an Inclusive Society project, which addresses the challenges of the digital divide for people with disabilities of all ages. Design/methodology/approach: The project employs a number of activities and approaches which involve people with disabilities and other stakeholders, in order collect scientific knowledge, views, suggestions and experiences that will help in bridging the digital divide. These include literature review and qualitative methodologies of data collection, such as interviews with stakeholders, focus groups and living labs. Findings: The benefits of (assistive) technology in the lives of people with disabilities are highly appreciated. However, a number of barriers, including lack of digital skills are identified. Thus the development of (assistive) technology competencies programmes is suggested. In addition, there is evidence of the need to further involve all stakeholders and increase awareness. Social implications: The most important implication of the project is the production of the manifesto against the digital divide. With this document the project consortium justifies for action on raising awareness regarding the rights of persons with disabilities of all ages to be digitally included. Originality/value: The value of the project lies upon the publication of the manifesto against the digital divide, which has already been endorsed by a number of organisations in Europe and elsewhere, with the aspiration of influencing policy makers and practitioners to collaborate in order to bridge the digital divide.